2022
DOI: 10.11622/smedj.2022039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Singapore lung cancer patients who miss out on lung cancer screening recommendations

Abstract: Introduction: The National Lung Screening Trial (NLST) identified individuals at high risk for lung cancer and showed that serial low-dose helical computer tomographic scans (CT) were able to identify lung cancer at an earlier stage and also demonstrated mortality reduction. However, there has been little evidence regarding the effectiveness of the Lung Cancer Screening Criteria in the Asian population. Methods: To determine lung cancer patients who miss out on Lung Cancer screening criteria, we performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A recent retrospective audit in a single hospital of Singapore patients (N=126) showed that 85.4% of those presenting at an advanced stage would have benefited from an LDCT based on NLST criteria. 16 However, a trade-off needs to be acknowledged, in that this proposed targeted high-risk screening approach will probably not capture the subpopulation of East Asian non-smoking lung adenocarcinoma cancers. 16,17 Non-smokers represented a third of patients (33.3%) diagnosed with lung cancer in the hospital audit.…”
Section: Implementation Of the Lung Cancer Screening Programmementioning
confidence: 99%
See 2 more Smart Citations
“…A recent retrospective audit in a single hospital of Singapore patients (N=126) showed that 85.4% of those presenting at an advanced stage would have benefited from an LDCT based on NLST criteria. 16 However, a trade-off needs to be acknowledged, in that this proposed targeted high-risk screening approach will probably not capture the subpopulation of East Asian non-smoking lung adenocarcinoma cancers. 16,17 Non-smokers represented a third of patients (33.3%) diagnosed with lung cancer in the hospital audit.…”
Section: Implementation Of the Lung Cancer Screening Programmementioning
confidence: 99%
“…16 However, a trade-off needs to be acknowledged, in that this proposed targeted high-risk screening approach will probably not capture the subpopulation of East Asian non-smoking lung adenocarcinoma cancers. 16,17 Non-smokers represented a third of patients (33.3%) diagnosed with lung cancer in the hospital audit. 16 Apart from smoking, additional risk factors in Asian populations have been described, including a positive family history 18 and environmental carcinogen signatures, 19 which may need further research as a distinct cohort from the high-risk smoking population.…”
Section: Implementation Of the Lung Cancer Screening Programmementioning
confidence: 99%
See 1 more Smart Citation
“…7 A local lung cancer study demonstrated that many females and non-smokers diagnosed with lung cancer did not fit US National Lung Screening Trial criteria, a finding observed across other Asia Pacific countries. 8 The Lung Cancer Consortium Singapore (LCCS) SOLSTICE screening study is currently ongoing to assess the early detection of lung cancer (https://lccs.com.sg).…”
mentioning
confidence: 99%